2021
DOI: 10.3389/fmed.2021.608760
|View full text |Cite
|
Sign up to set email alerts
|

High SVR12 With 8-Week Course of Direct-Acting Antivirals in Adolescents and Children With Chronic Hepatitis C: A Comprehensive Analysis

Abstract: Direct-acting antiviral (DAA) treatment for 8 weeks has a sustained virological response rate in adults with chronic hepatitis C. We have conducted a systematic review and meta-analysis to compare the efficacy and safety of the 8-week vs. 12/24-week DAA treatment in adolescents and children with CHC. The PubMed, Web of Science, and Cochrane databases were searched for the relevant articles from January 1, 2017 to August 28, 2020 and further screened for literature reviews on April 1, 2021. Pool proportions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Few small observational studies, which have used different DAA combinations, have shown that the treatment outcome with 8 weeks of duration is comparable to 12 weeks of therapy [11][12][13][14][15][16][17]. Till date, we do not have any randomized controlled trial comparing the 8 versus 12 weeks of sofosbuvir/velpatasvir combination for HCV treatment.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Few small observational studies, which have used different DAA combinations, have shown that the treatment outcome with 8 weeks of duration is comparable to 12 weeks of therapy [11][12][13][14][15][16][17]. Till date, we do not have any randomized controlled trial comparing the 8 versus 12 weeks of sofosbuvir/velpatasvir combination for HCV treatment.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Shorter duration DAA-based regimens, if sufficient to achieve virologic cure, might improve treatment completion rates and save cost. Fu et al [33 ▪ ] found high curative rates with 8 weeks of therapy for both GLE/PIB and several SOF-based regimens.…”
Section: Direct-acting Antiviral Regimens In Real-world Settings and ...mentioning
confidence: 99%